Injectable Peptide Liquid Crystal Hydrogel with Hierarchical Microstructure Directs Myoblast Alignment and Potentiates Muscle Functional Recovery - Huang, Rong; Cai, Chuang; Cheng, Wei‐Wei; Cheng, Yin‐Jia; Liu, Wen‐Long; Ma, Yi‐Han; Zhang, Ai‐Qing; Qin, Si‐Yong (Advanced functional materials, 2025)
A highly hierarchical microstructure with aligned myofibers is a hallmark of native skeletal muscle. To treat volumetric muscle loss (VML), the development of tissue scaffolds that replicate the hierarchically aligned microstructures of the native muscle environment is both promising and challenging. Moreover, effective scaffolds should possess tunable components that enable specific functional modulations. This study proposes an injectable, self‐assembling peptide liquid crystal (LC) hydrogel with hierarchical fiber alignment to support skeletal muscle regeneration. To emulate the physicochemical functions of skeletal muscle, Ti 3 C 2 T x MXene is incorporated as an exogenous component to enhance the mechanical strength, anti‐inflammatory activity, and electrical conductivity of the LC hydrogel. The resulting Ti 3 C 2 T x /LC peptide hydrogel effectively guides myoblast alignment and promotes myogenic differentiation and angiogenesis. Compared to its unaligned non‐liquid crystal (NLC) hydrogel counterpart, the aligned Ti 3 C 2 T x /LC hydrogel with a hierarchical microstructure significantly enhances new muscle tissue formation and functional recovery in a Sprague–Dawley (SD) rat model of VML. This study offers a robust and practical strategy for fabricating aligned hydrogel scaffolds with substantial potential in muscle tissue engineering and regenerative medicine.